The Effect of Training in Various Kinds of Active Bottom Drill Drills on Increasing Pasing Accuracy Down Onupper Class Boys Students of Primary School Perumnas Condongcatu - Dermawan, Budi (Berpusi Publishing, 2024)
This study aims to determine the effect of various types of active lower passdrill drills on increasing the accuracy of the lower pass in the volleyballgame of upper class male students at SD Perumnas Condongcatur. Thisresearch uses an experimental method, the research design is